2022
DOI: 10.1101/2022.08.16.22278877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COADREADx: A comprehensive algorithmic dissection unravels salient biomarkers and actionable insights into the discrete progression of colorectal cancer

Abstract: Colorectal cancer remains an increasingly common disease with uncommon burden of disease, heterogeneity in manifestation, and no definitive treatment. Against this backdrop, renewed efforts to unravel the genetic drivers of colorectal cancer progression are paramount. Early-stage detection of cancer increases success of treatment as well as prognosis. Here, we have executed a comprehensive computational workflow aimed at uncovering the discrete stagewise genetic drivers of colorectal cancer progression. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…32 Sangeetha Muthamilselvan et al 33 found that FBN1 as a stage I-salient hyper methylated gene, FOXG1 as a stage II-salient hyper methylated gene, HCN1 as stage III-salient hyper methylated gene, and NELL1, ZNF135, FAM123A, LAMA1 as stage IV-salient hyper methylated genes, which would drive the progression of CRC. Ashok Palaniappan and Sarathi 34 reported that CRLF1, CALB2 as stage I-specific differentially expressed genes (DEGs), GREM2, ADCY5, PLAC2, and DMRT3 as stage II-specific DEGs, PIGR and SLC26A9 as stage III-specific DEGs, and GABRD, DLX3, CST6, and HOTAIR as stage IV-specific DEGs, which were identified as progression-significant biomarkers. However, overall trend changes in gene expression in stages I to IV of CRC have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…32 Sangeetha Muthamilselvan et al 33 found that FBN1 as a stage I-salient hyper methylated gene, FOXG1 as a stage II-salient hyper methylated gene, HCN1 as stage III-salient hyper methylated gene, and NELL1, ZNF135, FAM123A, LAMA1 as stage IV-salient hyper methylated genes, which would drive the progression of CRC. Ashok Palaniappan and Sarathi 34 reported that CRLF1, CALB2 as stage I-specific differentially expressed genes (DEGs), GREM2, ADCY5, PLAC2, and DMRT3 as stage II-specific DEGs, PIGR and SLC26A9 as stage III-specific DEGs, and GABRD, DLX3, CST6, and HOTAIR as stage IV-specific DEGs, which were identified as progression-significant biomarkers. However, overall trend changes in gene expression in stages I to IV of CRC have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we compared the expression of known cancer related genes (i.e. tumour suppressor and oncogenes) in stem cells between UC and PSC-IBD, in both inflamed and non-inflamed states [29]. For both the non-inflamed state and the inflamed state, we found that similar ratios of tumour suppressor to oncogenes were upregulated in stem cells in PSC-IBD and UC.…”
Section: Differential Expression Analysis Reveals Differences Between...mentioning
confidence: 91%